Self-assembly of fluorinated sugar amino acid derived alpha,gamma-cyclic peptides into transmembrane anion transport - Burade, Sachin S.; Saha, Tanmoy; Bhuma, Naresh; Kumbhar, Navanath; Kotmale, Amol; Rajamohanan, Pattuparambil R.; Gonnade, Rajesh G.; Talukdar, Pinaki; Dhavale, Dilip D. (Organic Letters, 2017)
Syntheses of fluorinated sugar amino acid derived alpha,gamma-cyclic tetra- and hexapeptides are reported. The IR, NMR, ESI-MS, CD, and molecular modeling studies of cyclic tetra- and hexapeptides showed C-2 and C-3 symmetric flat oval- and triangular-ring shaped, beta-strand conformations, respectively, which appear to self assemble into nanotubes. The alpha,gamma-cyclic hexapeptide (EC50 = 2.14 mu M) is found to be a more efficient ion transporter than alpha,gamma-cyclic tetrapeptide (EC50 = 14.75 mu M). The anion selectivity and recognition of alpha,gamma-cyclic hexapeptide with NO3- ion is investigated.